Clinical Features and Drug-Resistance Profile of Urinary Tuberculosis in South-Western China: A Cross-sectional Study. Issue 19 (May 2016) - Ye, Yuanxin; Hu, Xuejiao; Shi, Yunying; Zhou, Juan; Zhou, Yi; Song, Xingbo; Xie, Yi; Lu, Xiaojun; Wang, Lanlan; Ying, Binwu; Chen, Xuerong
Abstract : Abstract: To investigate the epidemiology, clinical features, and drug-resistance profile of urinary tuberculosis (UTB) in south-western China to improve UTB diagnostics. After the screening of 1036 cases of suspected UTB, 193 patients with UTB were enrolled during 2009 to 2014. Urine samples were collected for routine urinalysis, smear, tuberculosis DNA (TB-DNA) detection, and drug-resistant analysis, whereas blood samples were collected for erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and renal function evaluation. Clinical features (such as symptoms and outcome) and imageology results (such as B ultrasonic, computerized tomography, intravenous pyelography, and renography) were also collected and analyzed to investigate the epidemiology, clinical features, and drug-resistance profile. The most common presenting symptoms were urinary irritation (61.1%) and lumbago (49.2%). High proportions of microscopic hematuria (63.2%) and microscopic proteinuria (45.6%) were also observed. The positive rate for TB-DNA was 66.3%. The positive rate for culture was 13.1% and for smear it was 9.8%. The abnormal outcome rates of the computerized tomography, ultrasonography, intravenous pyelography, and the nephrogram were 76.9%, 70.1%, 29.8%, and 37.0%, respectively. The total rate of drug-resistant TB (resistant to at least 1 drug) was 39.7%, of which 20.7% was multidrug-resistance TB. The most prevalent mutation sites were katG S315T1, rpoB S531L, and gyrA D94G. We observed a serious epidemic of drug-resistant UTB and a substantial number of new UTB cases with multidrug resistance TB. Molecular diagnostics is crucial in the definite diagnosis of UTB, and our finding is a supplement and further confirmation of polymerase chain reaction usage for TB diagnosis. We recommend real-time polymerase chain reaction for TB-DNA identification instead of culture, and GenoType tests (MTBDRplus and MTBDRsl assay) for drug resistance as routine assays for patients with suspected UTB.